Isotopic labelling applied to the infrared spectra of metal complexes - Niven, Margaret Lilian (Department of Chemistry, 2016)
An ir investigation of a series of 2-aminomethylpyridine complexes of first transition metal(II) perchlorates, tetrafluoroborates, halides and thiocyanates is reported. Comparisons with the spectra of related complexes of 2,2'-bipyridine and ethylenediamine together with metal-ion substitution, deuteration and ¹⁵N isotopic labelling of the amino group in 2-aminomethylpyridine enable reliable band assignments to be made. The study shows that in complexes of the type M(amp)nX₂, metal-to-amino-nitrogen stretches occur at frequencies greater than 350 cm⁻¹ , while the metal-to-pyridine-nitrogen stretches are generally below 300 cm⁻¹, the assignment of the latter being generally complicated by the presence of metal-to-halogen vibrations. In addition to an x-ray crystallographic investigation of the complex [Ni(amp)₃](BF₃ ₄)₂, considerable structural information about these complexes is obtained from correlations between the number of M-L vibrations observed in the far ir and those predicted for localized molecular point symmetries on a group theoretical basis.